Influence of different commercial active dry yeasts on histaminol production during wine alcoholic fermentation. (9th April 2017) - Bordiga, Matteo; Guzzon, Raffaele; Larcher, Roberto; Travaglia, Fabiano; Arlorio, Marco; Coïsson, Jean Daniel
Abstract: The performance of different selected yeast strains regarding the capacity to convert histidine into histaminol during fermentation has been described and discussed in a model grape must (Chardonnay). First, the activity of 10 commercial active dry yeast strains (ADY) in the native grape must both with and without a nitrogen supplementation has been compared. In the second set of fermentations, after selecting the four best‐performing strains, their performances using four different nitrogen sources have been tested. During fermentation process it was not possible to identify a common trend. In some cases, histaminol content appeared related to the nutrient supplementation, however, in other cases a different behaviour emerged. However, as shown by the experimental evidences, among the two variables considered the nature of yeast strain was slightly prevalent. Abstract : The activity of 10 commercial active dry yeast strains (ADY) has been investigated. Different nitrogen sources addition to ADY affects the formation of histaminol.